Recent Advances in 1D Electrospun Nanocatalysts for Electrochemical Water Splitting. Issue 2 (16th November 2020) - Zhang, Longcheng; Zhao, Haitao; Xu, Siran; Liu, Qian; Li, Tingshuai; Luo, Yonglan; Gao, Shuyan; Shi, Xifeng; Asiri, Abdullah M.; Sun, Xuping
Abstract : Electrochemical water splitting, as a promising sustainable‐energy technology, has been limited by its slow kinetics and large overpotential. This shortcoming necessitates the design of 1D nanocatalysts with large surface area, high electronic conductivity, and easily tunable composition. Herein, recent progress about electrocatalytic water splitting based on the advanced electrospun nanomaterials is reviewed. First, the related fundamentals of electrochemical water splitting according to two main aspects are discussed as follows: hydrogen evolution reaction and oxygen evolution reaction. Second, the structure design and the electrocatalytic properties of electrospun nanomaterials according to difference in component (including single metal‐based electrocatalysts, metal alloy‐based electrocatalysts, metal oxide‐based electrocatalysts, metal sulfide‐based electrocatalysts, metal phosphide‐based electrocatalysts, metal carbide‐based electrocatalysts, etc.) are summarized. Finally, the future perspectives and challenges for designing next‐generation 1D electrospun nanocatalysts for electrochemical water splitting are concluded. Abstract : Herein, recent advances in structure design and the catalytic properties of electrospun nanomaterials for electrochemical water splitting are summarized.